Efeitos da adição de resíduos de cerâmica vermelha e gesso da construção civil nas propriedades do cimento portland - Santos, Francisco Robson dos (Universidade Federal Rural do Semi-Árido, 2019)
The present work has as main objective to insert residues of red ceramics and recycled plaster of the civil construction in the process of Portland cement Pozzolanic. They partially replace the cement clinker, providing a double benefit to the environment: immobilize industrial waste adding value and reduce the consumption of cement that is a major emitter of polluting gases and consumer of natural resources. Laboratory tests were performed using a factorial design using Software Statistica 12.0. X-Ray fluorescence spectrometry, chemical analysis of pozzolanic activity of red ceramics (IAP), mechanical tests, porosity, resistance to sulfates and alkali-aggregate reaction were used. Through the tests, it was possible to attest the viability of the residues in the cement production, as well as its characteristics and properties. It was observed that up to 30% of the addition of red ceramic residue combined with 4.5% of gypsum does not affect the quality of the cement obtained when compared to the requirements of the current norms
Keywords: Sustentabilidade; Resíduos; Reciclagem; Cimento ecológico; Sustainability; Waste; Recycling; Ecological cement; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA